Soft Robotics for Human-Robot Interaction Applications - Raghu Kalyana (International Journal of Intelligent Systems and Applications in Engineering, 2023)
As the prevalence of robots in society rises, the necessity for interaction with them is becoming imperative. The domain of Human-Robot Interaction (HRI) has gained significance as robots increasingly undertake repetitive and laborious tasks. Recently, the domain of soft robotics has shown significant growth in both research and commercialization. Industry 5.0 emphasizes human-robot cooperation, hence advancing the domain of soft robotics. Nonetheless, the human-robot interaction for soft robotics remains in its embryonic phase. This paper reviews and discusses the implementation of human-robot interaction (HRI) in soft robots. We first examine the control, design, materials, and fabrication of soft robots. This will elucidate the nature of the interaction. Subsequently, we examine the many input and output modalities used in human-robot interaction (HRI). The literature provides a detailed discussion of the applications of Human-Robot Interaction (HRI) in soft robots. The constraints of human-robot interaction (HRI) for soft robots and the many research possibilities within this domain are examined comprehensively. It is concluded that there exists significant potential for the advancement of human-robot interaction in soft robotics.